Differentially methylated DNA regions in early childhood wheezing: An epigenome‐wide study using saliva. Issue 3 (17th February 2019) - Popovic, Maja; Fiano, Valentina; Fasanelli, Francesca; Trevisan, Morena; Grasso, Chiara; Assumma, Manuela Bianca; Gillio‐Tos, Anna; Polidoro, Silvia; De Marco, Laura; Rusconi, Franca; Merletti, Franco; Zugna, Daniela; et al.
Abstract: Background: Epigenetics may play a role in wheezing and asthma development. We aimed to examine infant saliva DNA methylation in association with early childhood wheezing. Methods: A case‐control study was nested within the NINFEA birth cohort with 68 cases matched to 68 controls by sex, age (between 6 and 18 months, median: 10.3 months) and season at saliva sampling. Using a bumphunting region–based approach, we examined associations between saliva methylome measured using Illumina Infinium HumanMethylation450k array and wheezing between 6 and 18 months of age. We tested our main findings in independent publicly available data sets of childhood respiratory allergy and atopic asthma, with DNA methylation measured in different tissues and at different ages. Results: We identified one wheezing‐associated differentially methylated region (DMR) spanning ten sequential CpG sites in the promoter‐regulatory region of PM20D1 gene (family‐wise error rate < 0.05). The observed associations were enhanced in children born to atopic mothers. In the publicly available data sets, hypermethylation in the same region of PM20D1 was consistently found at different ages and in all analysed tissues (cord blood, blood, saliva and nasal epithelia) of children with respiratory allergy/atopic asthma compared with controls. Conclusion: This study suggests that PM20D1 hypermethylation is associated with early childhood wheezing. Directionally consistent epigenetic alteration observed in cord blood and other tissues at older ages in children with respiratory allergy and atopic asthma provides suggestive evidence that a long‐term epigenetic modification, likely operating from birth, may be involved in childhood atopic phenotypes.